The Impact of Human Resources Management, Collaboration, Partnership with Empowerment Approach Mediating on Sustainability of FMSRB Program Asset Management - Owin Jamasy, Djamaludin; Daud, Restuardy; Movianto, Gunawan Eko; Novianty, Eva; Sulistyaningsih, Dyah; Pranoto, Yuni; Amirudin, Andi; Pangaribuan, Herbert; Wajdi, Farid; Khairun Nisa, Mohd Arshad (2023)
This study aims to discover the correlation and the impact of human resources management, collaboration, and partnership with the empowerment variable mediating on sustainability of Flood Management in Selected River Basins (FMSRB) program assets. The results of the reliability testing (Cronbach’s Alpha’s analysis) to 5 study variables are very reliable and consistent with a score approaching 1 (Human Resources Management/HRM = 0.967. Collaboration = 0.941. Partnership = 0.939. Empowerment = 0.950. Sustainability= 0.952). Furthermore, through the convergent validity calculation, a significant correlation among the variables was discovered. There is a significant direct correlation of HRM with the Empowerment approach mediation to the sustainability of program assets management (β 0.141, p-0.038), as well as the Partnership (β 0.205, p-0.012); whereas the collaboration with the empowerment approach mediating on sustainability of program assets management, the direct correlation was rejected (B 0.005, p-0.067). Based on the results of the study, it is recommended that the sustainability of FMSRB program assets management will be able to take place if the entire stakeholders have commited to the implementation of human resources management, the improved quality of collaboration and quality of empowerment approach-based partnership.